Pengaruh Kepemimpinan dan Komitmen Karyawan Terhadap kinerja Organisasi (Survey Pada Dinas Kebudayaan dan Pariwisata Provinsi Riau) - Tris Pratama; Nuryanti '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conductedon Dinas Kebudayaan dan Pariwisata Provinsi Riau in order to determinethe influences Leadership and Employee Commitment either simultaneously orpartially on Performance of Organizational in Dinas Kebudayaan dan Pariwisata Provinsi Riau. The methodologyin this studyis: Leadership and Employee Commitment significant influenceon Performance of Organizational Dinas Kebudayaan dan Pariwisata Provinsi Riau and thedominant factoraffectingthe Performance of Organizational is Leadership. While thepopulationin this studyistheemployees on Dinas Kebudayaan dan Pariwisata Provinsi Riau whichamounted to145people, witha total sample of 106 respondents. Multiple Linear RegressionAnalysismethodby usingSPSSversion17. Simultaneous regression (F test) showed that the independent variables studied (Leadership and Employee Commitment) together (simultaneously) have a significant influence on the dependent variable (Performance Organizational). The magnitude of the influence that (R2) by the two independent variables together against the dependent variable was 50,9%, while the remaining 49,5% is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (leadership and employee Commitment) has a significant influence on Dinas Kebudayaan dan Pariwisata Provinsi Riau the dependent variable (performance organizational). Dominant variables affecting performance organizational in Dinas Kebudayaan dan Pariwisata Provinsi Riau is Leadership where the value of t-counted highest compared with other independent variables.Keywords: Leadership, Employee Commitment and Performance Organizational